1998
DOI: 10.1002/j.2161-1882.1998.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Attitudes Toward Diversity and Overall Satisfaction of University Students by Race

Abstract: Dario 0. Prieto There is considerable evidence that campus climate has a great deal to do with the success or failure of students in higher education. Astin (1 993) and Pascarella and Terenzini ( 1 991) demonstrated the value of involvement on campus for students and the importance of programs to encourage that involvement. Sedlacek ( I 996) has shown the importance of community For what he called "nontraditional students," those from racial or cultural groups other than White, middle-class, young, and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 3 publications
2
42
1
Order By: Relevance
“…With respect to antecedents, a number of individual and environmental factors that affect SS and development have been proposed. Individual characteristics may include grades (Centra and Rock 1971), gender (Drew and Work 1998) and ethnicity (Helm, Sedlacek, and Prieto 1998). For example, many instructors believe that there is, to some extent, a positive relationship between the final course grade and the level of overall satisfaction with this course.…”
Section: Student Satisfactionmentioning
confidence: 99%
“…With respect to antecedents, a number of individual and environmental factors that affect SS and development have been proposed. Individual characteristics may include grades (Centra and Rock 1971), gender (Drew and Work 1998) and ethnicity (Helm, Sedlacek, and Prieto 1998). For example, many instructors believe that there is, to some extent, a positive relationship between the final course grade and the level of overall satisfaction with this course.…”
Section: Student Satisfactionmentioning
confidence: 99%
“…Such exposure to racial issues is likely to have important consequences for students. Research by Helm, Sedlacek, and Prieto (1998) suggests that the way race is discussed and perceived on campus has implications for the social and academic adjustment for both minority and majority group members. As such, it is important to investigate whether White students' perceptions of the overall racial climate of their campus have a similar association with their social adjustment and integration on campus as it does for ethnic minority students.…”
Section: Racial Climate and Intergroup Relations On College Settingsmentioning
confidence: 99%
“…However, there is limited and conflicting evidence concerning the association between race and satisfaction with college. Several studies have found significant race differences in satisfaction (Ancis, Sedlacek, and Mohr, 2000;Eimers and Pike, 1997;Helm, Sedlacek, and Prieto, 1998;Rorhlick, Alvarado, Zaruba, and Kallio, 1998;Sanders and Burton, 1996;Umbach and Porter, 2002) but others have not (Knox et al, 1992;Thomas and Galambos, 2004). Further, most of the research designs provide limited understanding of race-associated differences in the processes shaping satisfaction.…”
Section: Introductionmentioning
confidence: 99%